2021
DOI: 10.1186/s12912-021-00568-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between self-efficacy and general health: a cross-sectional study of the nursing population

Abstract: Background The present research aimed to explore the association of self-efficacy and general health among nurses. Methods This was a descriptive-analytical. A total of 470 nurses were selected through the stratified sampling method. To collect the required data, GSE-10 and GHQ-28 were used. Independent-sample T-test, Pearson correlation coefficient, Chi-squared test, and regression were also used to analyze the obtained data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
(33 reference statements)
0
11
2
Order By: Relevance
“…The high efficacy value of nurses in this study also gives an idea of the health of nurses in the hospital where the research was conducted,that nurses who have a high score of efficacy, then social function in the context of general health is positive. This is according to the results of the study about the correlation of self-efficacy and general health nurses explain that self-efficacy and social function in general health are significantly correlated which indicates that nurses with positive self-efficacy have high self-efficacy and social function significantly improves the health of nurses, so it is important to anticipate problems related to social functions such as limited support resources and conflicts at work (Dadipoor et al, 2021).…”
Section: Discussionmentioning
confidence: 70%
“…The high efficacy value of nurses in this study also gives an idea of the health of nurses in the hospital where the research was conducted,that nurses who have a high score of efficacy, then social function in the context of general health is positive. This is according to the results of the study about the correlation of self-efficacy and general health nurses explain that self-efficacy and social function in general health are significantly correlated which indicates that nurses with positive self-efficacy have high self-efficacy and social function significantly improves the health of nurses, so it is important to anticipate problems related to social functions such as limited support resources and conflicts at work (Dadipoor et al, 2021).…”
Section: Discussionmentioning
confidence: 70%
“…Surprisingly, our results showed that the Lebanese nursing students scored high on the GSE scores. Those scores were higher than the Iranian (Dadipoor et al, 2021), Egyptian (Kassem, 2015), and…”
Section: Discussionmentioning
confidence: 72%
“…Surprisingly, our results showed that the Lebanese nursing students scored high on the GSE scores. Those scores were higher than the Iranian (Dadipoor et al, 2021), Egyptian (Kassem, 2015), and Chinese nursing students' scores (Cheng et al, 2020). A plausible explanation for those differences might be attributed to the concept of resilience among the Lebanese population.…”
Section: Discussionmentioning
confidence: 75%
“…The mediating effect accounted for 28.95%. In the prior study on nursing staff, self-efficacy greatly impacted anxiety and sleep disturbances during the COVID-19 pandemic (Simonetti et al, 2021) and even positively impacted all aspects of nurses' general health (Dadipoor et al, 2021). Researchers found that emotional intelligence, working pressure, self-efficacy, and autonomy were of great significance in improving nurses' job satisfaction and performance (Hwang and Park, 2022).…”
Section: Discussionmentioning
confidence: 99%